2020
DOI: 10.1053/j.gastro.2020.05.014
|View full text |Cite
|
Sign up to set email alerts
|

Symptom Profiles and Risk Factors for Hospitalization in Patients With SARS-CoV-2 and COVID-19: A Large Cohort From South America

Abstract: T he pandemic caused by a novel severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) can cause several gastrointestinal (GI) symptoms. A recent systematic review showed a prevalence of GI symptoms in 17.6%. The most frequent manifestations were anorexia (26.8%), diarrhea (12.5%), nausea/vomiting (10.2%), and abdominal pain (9.2%), 1 and recent reports showed the detection of viral RNA in stools for prolonged periods (70.3%). 1 We established the frequency and impact of GI symptoms, and viral presence i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
34
2
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 30 publications
(37 citation statements)
references
References 8 publications
0
34
2
1
Order By: Relevance
“…The pandemic of the novel coronavirus, the severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection (also known as coronavirus disease 2019, COVID-19) has infected more than 59 million individuals worldwide and caused more than 1.4 million deaths. Although the main manifestations of COVID-19 are related to respiratory symptoms, the compromise of multiple organs has been described in the literature, including the digestive system[ 1 ]. There are several gastrointestinal manifestations, including anorexia, diarrhea, nausea/vomiting, and abdominal pain.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The pandemic of the novel coronavirus, the severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection (also known as coronavirus disease 2019, COVID-19) has infected more than 59 million individuals worldwide and caused more than 1.4 million deaths. Although the main manifestations of COVID-19 are related to respiratory symptoms, the compromise of multiple organs has been described in the literature, including the digestive system[ 1 ]. There are several gastrointestinal manifestations, including anorexia, diarrhea, nausea/vomiting, and abdominal pain.…”
Section: Introductionmentioning
confidence: 99%
“…There are several gastrointestinal manifestations, including anorexia, diarrhea, nausea/vomiting, and abdominal pain. Those symptoms have a pooled prevalence of 17.6% and are frequently observed in hospitalized patients[ 1 , 2 ].…”
Section: Introductionmentioning
confidence: 99%
“…From 31 selected studies investigating a total of 53 538 patients with laboratory‐confirmed SARS‐CoV‐2 infection, the symptoms most frequently reported in association with COVID‐19 included fever, cough, sore throat, dyspnoea (including shortness of breath or tachypnoea), diarrhoea, nausea or vomiting, and myalgia or arthralgia (Table 3). 1,17,18,28,31,39,41–65 The literature also suggests that olfactory or gustatory dysfunction, particularly of sudden onset, can be key early manifestations of COVID‐19, 66,67 with the presence of hyposmia and hypogeusia potentially facilitating discrimination between COVID‐19 and other influenza‐like illnesses 68 …”
Section: Resultsmentioning
confidence: 99%
“…Similarly, this patient had diarrhea, indicating that patients with COVID-19 with diarrhea need ventilator support and intensive care more often than those without diarrhea 22 . The presence of gastrointestinal symptoms is associated with a higher risk of hospitalization, which becomes more pronounced as the severity of the disease increases 23 , 24 . Furthermore, 90% (9/10) of patients with diarrhea in this study were in the delayed discharge group, implying that the length of hospital stay was longer for patients with diarrhea than for those without diarrhea; however, this finding requires further verification in multicenter studies with a larger sample size.…”
Section: Discussionmentioning
confidence: 99%